Ida Umami - PENGEMBANGAN DAN PEMELIHARAAN KESEMPURNAAN INSANIAH MELALUI PENDIDIKAN BUDI PEKERTI ISLAMI - Ida Umami (Postgraduate State Islamic Institute (IAIN) Metro, 2015)
Character education is aimed at achieving the five goals. Firstly, it is to develop affective potency of the students in their context as human and citizen inheriting their nation character values. Secondly, it is to develop the noble habit and behavior which are in line with the universal values and the nation religious tradition. Thirdly, it is to strengthen the students’ leadership and their sense of responsibility as to the next generation of the nation. Fourthly, it is to develop the students’ competency so that they could be autonomous, creative, and possess nationality insight. Finally, it is to develop the school as a good learning environment so that it could support the growth of honesty, creativity, and friendship with the pride of nationality and dignity. Character education has three main functions. First, it functions to shape and develop the students’ potency so that they can have a good mind, be kind, and behave in line with the philosophical values of Pancasila. Second, it functions as refinement and strengthening the role of family, educational institution, society, and government to participate and be responsible in developing the citizens’ potency within the context of Islam.